A South African exploration into the impact of non-first additional English language barriers in higher education - Cornelius, Shine (The IIE, 2017)
In South African higher education, the most common language used is English. This means that language barriers are present due to the diversity of South Africa. The following research study was a South African exploration into the impact of non-first additional English language barriers in higher education. The aim of this study was to explore the impacts, effects and solutions to non-first additional English language barriers in higher education. The study took the form of Qualitative research, in which an Interpretivist approach was employed. Qualitative data was collected through a focus group interview and made use of a thematic analysis method. The data collected indicated that special education and lecturer training was needed to provide the tools and knowledge necessary to assist students. Furthermore, the data found that student motivation and sociocultural impacts had an impact on learning a new language. The first recommendation made for this study is to further research bilingual education in a higher educational environment. The second recommendation made for this study is to further research into student motivation and how to influence student motivation. The third recommendation made for this study is to further research into the socio-cultural impacts on learning a new language.
Keywords: Higher education, South Africa; English language; Language barriers